Explorating Flower Morphology and Pollen Types of Various Angiospermae Families from Huluduotamo Village, Gorontalo - Moh. Randy Putra Pratama Thalib; Nazwa S. Lamante; Indayani Tandililing; Rawiyanti Ibrahim; Linda K. Mahluk; Sri Layla Putri Ishak; Magfirah F. Mantali; Nazwa H. Djafar; Nurhayati S. Bano; Jusna Ahmad; Febriyanti Febriyanti (Universitas Labuhanbatu, 2025)
Huluduotamo village is one of the villages in Suwawa District, Bone Bolango Regency, Gorontalo Province. The village is situated in the middle of the countryside within the Suwawa district area. The potential of Huluduotamo village is the potential of natural resources; thus, the exploration of flower morphology and pollen types of various angiosperm families was carried out in the village. Therefore, this study aims to look at and figure out the shape of pollen from different plant families, mainly Malvaceae and Fabaceae, by looking at pollen units, aperture types, wall thickening, and exine decoration. We conducted the sampling in the Huluduotamo village, Gorontalo, using direct observation methods and descriptive analysis under a microscope. The study found that the pollen from the Hibiscus rosa-sinensis L. plant in the malvaceae family has a monad pollen unit, an apantoporate aperture type, thickening of the centrifugal wall, and decoration on the echinate exine. Some plants, like Caesalpinia pulcherrima L. in the Fabaceae family, have pollen that is made up of a single unit, an atricolporate aperture for the red variety and a parasyncolporate aperture for the yellow variety, and psilate axine decoration. The similarity of the monad pollen unit shows how angiosperm plants reproduce, while differences in aperture types and axine ornamentation show how the shape of the plant has changed to support reproduction. This research provides important information for the identification of plant species and supports flowering plants